Encyclopaideia 2007-2016. Introduction - Luca Ghirotto; Giovanna Malusà (Encyclopaideia, 2016)
From 20 years since its foundation, Encyclopaideia reflects on its history, changes, and newly gained identity. Encyclopaideia recognizes itself within Piero Bertolini's directions of meaning but, at the same time, has defined spaces of discontinuity which are so important for being faithful to a project historically connoted. The anniversary is, therefore, a pretext for both coming to terms with the past and reflecting about relaunches that will give future to the cultural and editorial project of Encyclopaideia and Phenomenological Education debate in Italy and abroad.